2011
DOI: 10.4067/s0718-58392011000100009
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, insecticidal, and antifungal activities of fruit essential oils of three colombian Zanthoxylum species

Abstract: This study determined the chemical composition of essential oils isolated from Zanthoxylum monophyllum (Lam.) P. Wilson, Z. rhoifolium Lam., and Z. fagara (L.) Sarg. fruits by steam distillation, as well as testing antifungal and insecticidal activities of essential oils as potential pesticides. Gas chromatography-mass spectrometry (GC/MS) analysis identified 57 compounds. The main constituents in Z. rhoifolium oil were β-Myrcene (59.03%), β-phellandrene (21.47%), and germacrene D (9.28%), the major constituen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 39 publications
(44 reference statements)
1
27
0
4
Order By: Relevance
“…Z. zanthoxyloïdes est considérée comme un antiparasitaire polyvalent interne et externe (Kerharo and Adam, 1974 ;Ngassoum et al, 2003). L'étude phytochimique des espèces du genre Zanthoxylum a montré la présence d'alcaloïdes de type variés, de lignanes, de coumarines, des amides, des tanins, des huiles essentielles et d'autres métabolites tels que : les flavonoïdes, les stérols et les terpènes (Kerharo and Adam, 1974 ;Dieguez et al, 2003;Patiño, 2004;Adesina, 2005;Prieto et al, 2011). Quant à N. laevis, elle renferme les grandes familles de composés tels que : des dérivés phénoliques (flavonoïdes, tanins, acides phénoliques, glucuronat de flavones et flavonols), des mucilages, des traces d'huiles essentielles, des alcaloïdes, des anthocyanes, des glucides, des dérivés quinoniques (naphtaquinones), des saponosides, des stéroïdes et triterpenoïdes, des quinones et des alcaloïdes associés à des pigments (Olounladé, 2005 ;Eyong et al, 2006).…”
Section: Effetunclassified
“…Z. zanthoxyloïdes est considérée comme un antiparasitaire polyvalent interne et externe (Kerharo and Adam, 1974 ;Ngassoum et al, 2003). L'étude phytochimique des espèces du genre Zanthoxylum a montré la présence d'alcaloïdes de type variés, de lignanes, de coumarines, des amides, des tanins, des huiles essentielles et d'autres métabolites tels que : les flavonoïdes, les stérols et les terpènes (Kerharo and Adam, 1974 ;Dieguez et al, 2003;Patiño, 2004;Adesina, 2005;Prieto et al, 2011). Quant à N. laevis, elle renferme les grandes familles de composés tels que : des dérivés phénoliques (flavonoïdes, tanins, acides phénoliques, glucuronat de flavones et flavonols), des mucilages, des traces d'huiles essentielles, des alcaloïdes, des anthocyanes, des glucides, des dérivés quinoniques (naphtaquinones), des saponosides, des stéroïdes et triterpenoïdes, des quinones et des alcaloïdes associés à des pigments (Olounladé, 2005 ;Eyong et al, 2006).…”
Section: Effetunclassified
“…Z. monophyllum was the most active, followed by Z. fagara and Z. rhoifolium. These results are attributable to the presence of some compounds that are in these fruits essential oils in low concentrations such as (E)-caryophyllene, T-muurolol, and α-cadinol, compounds that have been previously reported as antifungal substances by other researchers [113].…”
Section: Essential Oilsmentioning
confidence: 88%
“…Leaf and branch extracts from Z. rhoifolium presented contact and ingestion toxicity to leaf cutting ants. The biological activities of this plant were described (Negi et al, 2011;Medhi et al, 2013), but insecticidal activity was observed only for its fruit essential oil (Prieto et al, 2011). Alkaloids are the main active pharmacological constituents of this plant (Jullian et al, 2006), with promising molecules for the management of leaf cutting-ants (Bigi et al, 2004;Almeida et al, 2007).…”
Section: Resultsmentioning
confidence: 99%